Strategi Komunikasi Dalam Proses Negosiasi Penandatangan Kuasa Di Kantor Hukum Rolando Marpaung & Partners - Rachel Mia L. Lbn. Toruan; Evi Enitari Napitupulu; Nurhawati Simamora; Desti Murni Hayati Telaumbanua (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Communication is the basis of all human activities. Because without communication, interaction between humans, whether individually, in groups or organizations, is impossible. Most human interactions take place in interpersonal communication situations. Lobbying is an informal, persuasive effort carried out by one party (person, group, private sector, government) who has a particular interest to attract support from parties who have influence over the course of an interest. Negotiation is a bargaining process by negotiating with other parties to reach an agreement. Negotiation means discussing or having a discussion about something. So in the process, this communication will occur in two directions, namely involving the interested parties. The purpose of negotiation is to help the parties concerned to align their views and straighten out the problem. In addition, negotiations also often occur to resolve disputes.